The Influence of Instructional Leadership and School Culture on the Performance of Public Senior High Schools in Rembang Regency - Lestari, Endang Sri; Nurkolis; Nyoman, Ngurah Ayu (IQRO: Journal of Islamic Education, 2024)
This study analyzes the influence of instructional leadership and school culture on school performance in public senior high schools in Rembang Regency. Using a quantitative approach with a survey method, data were collected through questionnaires distributed to teachers and analyzed with multiple regression. The results show that instructional leadership contributes 12.3% and school culture 17.8% to school performance. Together, both variables explain 30.3% of the variability, with the remaining 69.7% influenced by other factors. Effective instructional leadership, characterized by a clear academic vision, supervision, and teacher empowerment, improves learning quality. A strong school culture, based on collaboration, discipline, and innovation, boosts teacher motivation and student achievement. The study confirms the crucial role of leadership and culture in educational success, emphasizing the need for principal leadership competencies and a positive school culture. Keywords: Instructional Leadership; School Culture; School Performance;